Climate Change and Dengue in Bangladesh: Public Health Challenges and Action Priorities - Md Abdus Salam (TAJ: Journal of Teachers Association, 2026)
Dengue is an increasingly important public health problem in Bangladesh, driven by climate variability, rapid urbanization, inadequate drainage, intermittent water supply, and weak environmental management. These factors support Aedes breeding and sustain transmission, making dengue a climate-sensitive urban health challenge rather than a purely seasonal vector-borne disease. This narrative review examines how climate change is influencing dengue transmission, burden, and control in Bangladesh, with attention to ecological drivers, surveillance limitations, diagnostic gaps, health-system strain, and policy responses. Rising temperatures, changing rainfall patterns, humidity shifts, and extreme weather events can lengthen transmission seasons and expand risk into new areas. Bangladesh has faced repeated outbreaks with substantial morbidity and mortality, reflecting the combined effects of climate vulnerability and dense urban exposure. However, fragmented surveillance, delayed diagnosis, limited laboratory capacity, and overstretched hospitals continue to hinder early detection and effective management. Structural barriers such as weak intersectoral coordination, overreliance on reactive vector control, and limited use of climate information further constrain response efforts. Priority actions include climate-informed early warning systems, sustained urban environmental management, stronger clinical preparedness, improved community engagement, and coordinated governance across health and non-health sectors. A preventive, multisectoral approach is essential to reduce transmission and strengthen Bangladesh’s resilience to climate-related health risks.